Carboxylation Reactions Using Carbon Dioxide as the C1 Source via Catalytically Generated Allyl Metal Intermediates - Fujihara, Tetsuaki; Tsuji, Yasushi (Frontiers in Chemistry, 2019)
The use of carbon dioxide (CO2) is an important issue with regard to current climate research and the Earth’s environment. Transition metal-catalyzed carboxylation reactions using CO2 are highly attractive. This short review summarizes the transition metal-catalyzed carboxylation reactions of organic substrates with CO2 via allyl metal intermediates. First, carboxylation reactions via transmetalation are reviewed. Second, catalytic carboxylation reactions using ally electrophiles and suitable reducing agents are summarized. The last section discusses the catalytic carboxylation reactions via addition reactions.